2021
DOI: 10.3390/jmse9101087
|View full text |Cite
|
Sign up to set email alerts
|

Erosive Degradation Study of Concrete Augmented by Mussel Shells for Marine Construction

Abstract: This work proposes a green material for artificial reefs to be placed in Galicia (northwest Spain) taking into account the principles of circular economy and sustainability of the ecosystem. New concrete formulations for marine applications, based on cement and/or sand replacement by mussel shells, are analyzed in terms of resistance to abrasion. The interest lies in the importance of the canning industry of Galicia, which generates important quantities of shell residues with negative environmental consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The incorporation of calcite and aragonite shells contribute to creating a dense calcium carbonate protective layer along the concrete's surface. This layer provides protection against chemical attacks from seawater (Camba et al, 2021). An important conclusion that can be extracted from the results is that the water absorption is lower when the medium arid is substituted, and when calcite predominates over aragonite.…”
Section: Results Of the Shell Analysis And Mechanical Testsmentioning
confidence: 92%
“…The incorporation of calcite and aragonite shells contribute to creating a dense calcium carbonate protective layer along the concrete's surface. This layer provides protection against chemical attacks from seawater (Camba et al, 2021). An important conclusion that can be extracted from the results is that the water absorption is lower when the medium arid is substituted, and when calcite predominates over aragonite.…”
Section: Results Of the Shell Analysis And Mechanical Testsmentioning
confidence: 92%
“…Cephalopods play a crucial role in Galicia [16][17][18][19]. The species with the greatest socioeconomic impacts on the Iberian Peninsula are the common octopus (Octopus vulgaris), cuttlefish (Sepia officinalis), and squid (Loligo vulgaris) [20].…”
Section: The Problem Of Cephalopods In Galicia: Evolution Of Artisana...mentioning
confidence: 99%
“…Besides, the use of seawater-based concrete has been considered as an effective approach to sustainable development in construction engineering where the construction materials and freshwater are inconvenient to access [1][2][3]. In this regard, the mechanical properties of newly developed seawater-based concrete in specific service conditions have become a source of concern due to the fact that some inorganic ions in seawater cause remarkable changes to the microstructure of concrete [3][4][5][6]. It has been reported that the introduction of seawater could lead to gains in early strength and shortening of solidification time of seawatermixed concrete, which is probably caused by the accelerated hydration process induced by the presence of chloride ions in seawater [7,8].…”
Section: Introductionmentioning
confidence: 99%